Long-Term Effects of Pediatric Acute Lymphoblastic Leukemia Chemotherapy: Can Recent Findings Inform Old Strategies? - Al-Mahayri, Zeina N.; AlAhmad, Mohammad M.; Ali, Bassam R. (Frontiers in Oncology, 2021)
During the last few decades, pediatric acute lymphoblastic leukemia (ALL) cure rates have improved significantly with rates exceeding 90%. Parallel to this remarkable improvement, there has been mounting interest in the long-term health of the survivors. Consequently, modified treatment protocols have been developed and resulted in the reduction of many adverse long-term consequences. Nevertheless, these are still substantial concerns that warrant further mitigation efforts. In the current review, pediatric-ALL survivors’ late adverse events, including secondary malignant neoplasms (SMNs), cardiac toxicity, neurotoxicity, bone toxicity, hepatic dysfunction, visual changes, obesity, impact on fertility, and neurocognitive effects have been evaluated. Throughout this review, we attempted to answer a fundamental question: can the recent molecular findings mitigate pediatric-ALL chemotherapy’s long-term sequelae on adult survivors? For SMNs, few genetic predisposition factors have been identified including TP53 and POT1 variants. Other treatment-related risk factors have been identified such as anthracyclines’ possible association with breast cancer in female survivors. Cardiotoxicity is another significant and common adverse event with some germline variants been found, albeit with conflicting evidence, to increase the risk of cardiac toxicity. For peripheral neurotoxicity, vincristine is the primary neurotoxic agent in ALL regimens. Some germline genetic variants were found to be associated with the vincristine neurotoxic effect's vulnerability. However, these were mainly detected with acute neuropathy. Moreover, the high steroid doses and prolonged use increase bone toxicity and obesity risk with some pharmacogenetic biomarkers were associated with increased steroid sensitivity. Therefore, the role of these biomarkers in tailoring steroid choice and dose is a promising research area. Future directions in pediatric ALL treatment should consider the various opportunities provided by genomic medicine. Understanding the molecular bases underlying toxicities will classify patients into risk groups and implement a closer follow-up to those at higher risk. Pharmacogenetic-guided dosing and selecting between alternative agents have proven their efficacy in the short-term management of childhood ALL. It is the right time to think about a similar approach for the life-long consequences on survivors.